Introducing the Condor Array Telescope. V. Deep Broad- and Narrowband Imaging Observations of the M81 Group - Kenneth M. Lanzetta; Stefan Gromoll; Michael M. Shara; David Valls-Gabaud; Frederick M. Walter; John K. Webb (The Astrophysical Journal Supplement Series)
We used the Condor Array Telescope to obtain deep imaging observations through the luminance broadband and He ii 468.6 nm, [O iii ] 500.7 nm, He i 587.5 nm, H α , [N ii ] 658.4 nm, and [S ii ] 671.6 nm narrowband filters of an extended region comprising 13 “Condor fields” spanning ≈ 8 × 8 deg ^2 on the sky centered near M81 and M82. Here we describe the acquisition and processing of these observations, which together constitute unique very deep imaging observations of a large portion of the M81 Group through a complement of broad- and narrowband filters. The images are characterized by an intricate web of faint, diffuse, continuum produced by starlight scattered from Galactic cirrus, and all prominent cirrus features identified in the broadband image can also be identified in the narrowband images. We subtracted the luminance image from the narrowband images to leave, more or less, only line emission in the difference images, and we masked regions of the resulting images around stars at an isophotal limit. The difference images exhibit extensive extended structures of ionized gas in the direction of the M81 Group, from known galaxies of the M81 Group, clouds of gas, filamentary structures, and apparent or possible bubbles or shells. Specifically, the difference images show a remarkable filament known as the “Ursa Major Arc;” a remarkable network of criss-crossed filaments between M81 and NGC 2976, some of which intersect and overlap the Ursa Major Arc; and details of a “giant shell of ionized gas.”